The making precise of a limiting theorem for additive functions, defined on the set of values of polynomial from certain sequences - Toleuov, G.; Fainleib, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ж. Толеуов, А. Файнлейб. Уточнение одной предельной теоремы для аддитивных функций, заданных на множестве значений полинома от некоторых последовательностейŽ. Toleuovas, A. Fainleibas. Ribinės teoremos adityvinėms funkcijoms polinomo reikšmių aibėje patikslinimas